2019
DOI: 10.1002/fam.2801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passenger blockage on smoke flow properties in longitudinally ventilated tunnel fires

Abstract: This paper investigates the effects of passenger blockage on smoke flow properties in longitudinally ventilated tunnel fires. A series of numerical simulations were conducted in a 1/5 small-scale tunnel with the different heat release rates (50-100 kW), longitudinal ventilation velocities (0.5-1 m/s), passenger blockage lengths (2-6 m), and ratios (0.17-0.267). The typical smoke flow properties in different tunnel fire scenarios are analyzed, and the results show that under the same heat release rate and longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Additionally, many scholars [22][23][24][25][26][27][28] have studied the influence of blockage on the smoke back-layering length. Haddad et al [29] reviews recent research advances relating to critical velocity and the back-layering length of tunnel fires, mainly analyzing the experimental and theoretical studies on the effects of blockage, inclination, and fire source location.…”
Section: Hmentioning
confidence: 99%
“…Additionally, many scholars [22][23][24][25][26][27][28] have studied the influence of blockage on the smoke back-layering length. Haddad et al [29] reviews recent research advances relating to critical velocity and the back-layering length of tunnel fires, mainly analyzing the experimental and theoretical studies on the effects of blockage, inclination, and fire source location.…”
Section: Hmentioning
confidence: 99%
“…Blockage ratio is another important factor affecting critical velocity. 24,25 Kang et al 26 conducted numerical simulation to investigate the effect of blockage ratio on critical velocity by using the hydraulic diameter as the characterized length. Their results indicated that the critical velocity decreased when the blockage ratio was increased.…”
Section: Introductionmentioning
confidence: 99%